2002
DOI: 10.1176/appi.ajp.159.7.1080
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications and Schizophrenia: Historical and Meta-Analytic Review

Abstract: Current methods of investigating the relationship between obstetric complications and schizophrenia are reaching the limit of their usefulness. Lack of statistical power to measure small and interactive effects and lack of detailed information about the prenatal period are major problems with current approaches. A combination of disciplines and approaches will be needed to elucidate the mechanisms underlying these small but important associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
677
3
41

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,009 publications
(750 citation statements)
references
References 126 publications
29
677
3
41
Order By: Relevance
“…20 The frequency of serious obstetric complications was not statistically different between male (N = 97) and female (N = 19) probands (Fisher's exact test P-value = 0.78). Concordant with several other reports and two meta-analyses, [21][22][23][24] age of onset was significantly lower among probands reporting significant obstetric complications (mean age of onset = 19.6 years) versus those who did not experience significant complications (mean age of onset = 22.0 years; t-test P-value = 0.0091), although the difference between male and female probands' ages of onset was not significant (t-test P-value = 0.31). Of the 29 probands with OCs rated as serious (McNeil-Sjostrom Scale scores X5 on a scale of 1-6), the most common OC was bleeding during pregnancy (nine probands), followed by extended labor duration (four probands), delivery problems and respiratory distress at birth (three probands each), use of high forceps, birth via emergency cesarean section, adverse fetal position, early gestational age at birth and extreme prematurity (p33 weeks)/very low birthweight (two probands each).…”
Section: Methodssupporting
confidence: 89%
“…20 The frequency of serious obstetric complications was not statistically different between male (N = 97) and female (N = 19) probands (Fisher's exact test P-value = 0.78). Concordant with several other reports and two meta-analyses, [21][22][23][24] age of onset was significantly lower among probands reporting significant obstetric complications (mean age of onset = 19.6 years) versus those who did not experience significant complications (mean age of onset = 22.0 years; t-test P-value = 0.0091), although the difference between male and female probands' ages of onset was not significant (t-test P-value = 0.31). Of the 29 probands with OCs rated as serious (McNeil-Sjostrom Scale scores X5 on a scale of 1-6), the most common OC was bleeding during pregnancy (nine probands), followed by extended labor duration (four probands), delivery problems and respiratory distress at birth (three probands each), use of high forceps, birth via emergency cesarean section, adverse fetal position, early gestational age at birth and extreme prematurity (p33 weeks)/very low birthweight (two probands each).…”
Section: Methodssupporting
confidence: 89%
“…Yun et al [19] showed that in an "ultra-high risk" group of 74 patients, a history of obstetric complications was not associated with increased risk for psychotic conversion. This finding is not inconsistent with the literature on the association of obstetrical complications and schizophrenia that shows a consistent relationship with relatively small effect sizes that only reach a statistical level of significance with large populations [16].…”
Section: Environmental Risk Factorssupporting
confidence: 73%
“…Aside from the clinical and genetic risk factors, there are several known environmental risk factors for schizophrenia that have been further elucidated in recent reviews [16][17][18]. These risk factors could act as a second "hit" that contributes to the emergence of the illness in a genetically vulnerable individual.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…We then categorized the associated risk and protective factors into three domains: pre-settlement factors (educational background, traumatic events, immigration process), post-settlement factors (time since resettlement, acculturative stress, social support, family relationships, socioeconomic status), and personal factors (individual characteristics, sex, age, condition). After that, we identified consistent risk and protective factors using an approach employed in previous systematic reviews (Cannon, Jones, & Murray, 2002; Fazel, Reed, Panter-Brick, & Stein, 2012): only those factors that were consistently found to be associated with mental health outcomes in the same direction in three or more studies were included. When at least one study reported the opposite association between the same factor and mental health outcome, the factor was excluded.…”
Section: Methodsmentioning
confidence: 99%